(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
According to Carlael, Biographies of the Great men arehalf a History. The Character and work of great men have immense importance inthe scientific study of History, because History gets richer from thecontribution of such great men. They give new dimensions to the society withtheir shrewdness and ambitions, while creating and leaving a new landmark inHistory. Chatrapati Shahu Maharaj heads the list of such great men. He was theperson, who changed the existing notions with his benevolent and righteousattribution towards the Maratha Empire. While studying the rise and developmentof his personality, we have to study the Saint Tradition of Maharashtra,Shahaji Raje, and the overall historical period from Chhatrapati ShivajiMaharaj to Maharani Tarabai. Chatrapati Shahu stands as the brightest star inthe darkness of the unfavourable situations prevailed in the medieval era.